App Inventor: ferramenta de autoria para a criação de aplicativos educacionais apropriados a crianças com Transtorno do Espectro Autista - TEA de Alto Funcionamento - Haslinger, Evelin; Santos Jr, Francisco Dutra dos; Silva, Patrícia F. da (Anais do Workshop de Desafios da Computação aplicada à Educação (DesafIE!), 2019)
This challenge arises as a consequence of studies and reflections on pedagogical practices with the use of ?educational software for mobile devices?. The possibilities of using this resource in the classroom may be favorable to the educator as a technology accessible to the inclusion of students with high-functioning autism spectrum disorder (ASD). Given this context, our goal is to develop a ?QUIZ? for mobile devices - using the APP-inventor app aimed at improving the social interactions of students with high- functioning autism. Therefore, we believe that the application of a ?QUIZ? with school daily expressions, may improve social interactions as well as communication, a common difficulty that ASD students presents.